Eksistensi Mutu Pendidikan Informal Bali Aga Era Revolusi Industri 4.0 - I Nengah Juliawan (UHN IGB Sugriwa Denpasar, 2020)
As the Balinese people of Bali Aga, the people of Tenganan Peringsingan custom village had a special characteristics and identities than Balinese people in common. One of them is having their own calendar system which is totally different with the Balinese people have in common. Beside calendar systems, another unique tradition they had was Matruna Nyoman. This tradition is initiation ceremony for adolescents who grow up to manhood. In the Matruna Nyoman process, the adolescents of Tenganan get their education of tradition with the hope to be able to control their self physically and mentally, so they can represent the characters of Hindu’s youth. In this writing, it was done the analysis based on the theory of religion stated by E. B. Tylor. According to him, the religiosity came from human being’s consciousness toward spiritual concepts. In the functional structural theory of Durhkeim, he stated that interpreting the whole societies in the function matter of the constituent elements, especially norms, customs, traditions, and institutions. The result of this research shows that each adolescent of Tenganan Pengringsingan is able to gather to a head their knowledge and skill, so they can do their social duties based on Awig-awig of Tenganan Peringsingan custom village.